Customer Engagement in Enhancing Customer Loyalty: Empirical Evidence Non-Muslim Customers of Bank Syariah Indonesia (BSI) KCP Tomoni - Yusuf, Hardianti; Ginanjar, Muh.; Arlinda, Mutiara (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: One of the strategies implemented to engage customers is the application of the customer engagement concept. The purpose of this research is to analyze the customer engagement strategy's impact on the loyalty of non-Muslim customers at Bank Syariah Indonesia (BSI) KCP Tomoni. Research Methods: The research method employed in this study is qualitative research from a phenomenological perspective. The findings derived from in-depth interviews will then be analyzed using the Interpretative Phenomenological Analysis (IPA) method. Results: The implementation of customer engagement with the indicators of cognitive attachment, attitudinal attachment, and behavioral attachment can foster a sense of loyalty among non-Muslim customers towards BSI KCP Tomoni. Conclusion: The customer engagement strategy at BSI KCP Tomoni effectively enhances non-Muslim customer loyalty through cognitive, attitudinal, and behavioral dimensions. This study underscores the importance of inclusive and customer-centered approaches in Islamic banking to sustain loyalty across diverse segments.